Loss of Selenoprotein Iodothyronine Deiodinase 3 Expression Correlates with Progression of Complete Hydatidiform Mole to Gestational Trophoblastic Neoplasia - St. Laurent, Jessica D.; Lin, Lawrence H.; Owen, David M.; Maestá, Izildinha [UNESP]; Castaneda, Arnold; Hasselblatt, Kathleen T.; Goldstein, Donald P.; Horowitz, Neil S.; Berkowitz, Ross S.; Elias, Kevin M. (Springer Nature, 2021)
To investigate if differences in imprinting at tropho-microRNA (miRNA) genomic clusters can distinguish between pre-gestational trophoblastic neoplasia cases (pre-GTN) and benign complete hydatidiform mole (CHM) cases at the time of initial uterine evacuation. miRNA sequencing was performed on frozen tissue from 39 CHM cases including 9 GTN cases. DIO3, DLK1, RTL1, and MEG 3 mRNA levels were assessed by qRT-PCR. Protein abundance was assessed by Western blot for DIO3, DLK1, and RTL1. qRT-PCR and Western blot were performed for selenoproteins and markers of oxidative stress. Immunohistochemistry (IHC) was performed for DIO3 on an independent validation set of clinical samples (n = 42) and compared to normal placenta controls across gestational ages. Relative expression of the 14q32 miRNA cluster was lower in pre-GTN cases. There were no differences in protein abundance of DLK1 or RTL1. Notably, there was lower protein expression of DIO3 in pre-GTN cases (5-fold, p < 0.03). There were no differences in mRNA levels of DIO3, DLK1, RTL1 or MEG 3. mRNA levels were higher in all CHM cases compared to normal placenta. IHC showed syncytiotrophoblast-specific DIO3 immunostaining in benign CHM cases and normal placenta, while pre-GTN cases of CHM lacked DIO3 expression. We describe two new biomarkers of pre-GTN CHM cases: decreased 14q32 miRNA expression and loss of DIO3 expression by IHC. Differences in imprinting between benign CHM and pre-GTN cases may provide insight into the fundamental development of CHM.
Keywords: Complete hydatidiform mole; Iodothyronine deiodinase 3; MicroRNA; Placenta